Comparison of Fluoride Levels in Tap and Bottled Water and Reported Use of Fluoride Supplementation in a United States–Mexico Border Community - Victory, Kerton R.; Cabrera, Nolan L.; Larson, Daniela; Reynolds, Kelly A.; Latura, Joyce; Thomson, Cynthia A.; Beamer, Paloma I. (Frontiers in Public Health, 2017)
Background: Compared to the general U.S. population, Arizona counties along the U.S.-Mexico Border have a higher prevalence of dental caries, which can be reduced with adequate fluoride exposure. Because of concern regarding local tap water quality, fluoride-free bottled water consumption is common in this region, raising concern that families are not receiving adequate fluoride to promote dental health. Objective: To evaluate the levels of fluoride in tap and bottled water as well as the use of fluoride supplements in an Arizona Border community. Methods: Low-income Latino households (n=90) who report use of bottled water as their primary source of water intake were recruited. Participants completed a questionnaire about their and their children’s dental histories and use of fluoride supplements. Water samples (bottled and tap) were collected from a subset of households (n=30) for analysis of fluoride. Results: Fluoride detection levels were significantly greater (p=0.02, Fisher’s exact test) in tap water (average = 0.49 mg/dL) than in bottled water, yet, the majority (22/30) were below the range for optimal dental health (0.7-1.2 mg/L). Concentration of fluoride in the majority (29/30) of bottled-water samples was below the quantitative detection limit of 0.4 mg/L. Children were significantly less likely to have dental caries if they received fluoride varnishing treatments (p=0.01, Fisher’s exact test), lived in households that reported using fluoridated mouthwash (p<0.001, Fisher’s exact test), their parents received fluoride education (p=0.01, Fisher’s exact test), and their parents reported visiting a dentist yearly (p<0.001, Fisher’s exact test). Furthermore, none of the participants reported receiving recommendations from healthcare providers about fluoride supplementation or variance in content by the type of water consumed. Conclusion: Although fluoride was significantly more likely to be detected in tap than bottled water, neither water source in this Border community is likely to provide enough fluoride for optimal dental health. Low-income children in this region may benefit from regular access to fluoride varnishing treatments and/or use of fluoridated mouthwash, interventions that could be tested in future well-designed trials.